Case of left hip acute pediatric septic arthritis - polymicrobial etiology - Mathiyoth Chalil, Aghosh; Kurup, Karan K.; Eapen, Febi; Hashim, Suhail; Prince, George (International Journal of Research in Orthopaedics, 2023)
Septic arthritis is a true orthopedic emergency, involving a severe bacterial, viral, or fungal joint infection that triggers inflammation and the degeneration of joint tissues. It typically affects joints such as the knee, hip, shoulder, or wrist. Early diagnosis and treatment are crucial to avoid long-term complications. Herein, we describe the case of an 8-year-old male patient who presented with complaints of spontaneous onset of hip pain and an abnormal gait. The patient was diagnosed with left hip septic arthritis and underwent a left hip arthrotomy under general anesthesia (GA). The patient was administered intravenous antibiotics for 21 days while being kept on non-weight-bearing mobilization. After 3 weeks, the patient's intravenous antibiotics were switched to oral antibiotics for the next 3 weeks. On the second follow-up visit, the patient showed significant improvement, with laboratory findings within normal limits.